RANCANGAN LKPD BIOLOGI SMA BERBASIS RISET IDENTIFIKASI BAKTERI PADA TANAH TERCEMAR LIMBAH MINYAK BUMI - Abigail Vania Dela Rosa Agus; Sri Wulandari; L.N. Firdaus L.N. Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Pollution of soils due to contamination of petroleum wastes is certain to affect the balance of soil ecosystems. Soil is one of the most polluted environmental factors. Therefore, the type of bacteria capable of becoming bioremediation agents on contaminated soil is important to learn. This study aims to produce LKPD Learning class X Biology SMA by utilizing the results of studies on the identification of bacteria on contaminated soil waste oil. For this purpose, a survey was conducted in Minas Jaya Village, Siak Regency, Riau Province in April-June 2017. Determination of sampling location by considering the soil contaminated with earth's waste from oil wells. At each point of sampling, 3 captures were taken with different soil depths of 10 cm, 20 cm, and 30 cm. Data were analyzed descriptively. The results obtained are 5 types of bacteria, namely Bacillus sp, Enterobacter sp, Klebsiella sp, Pseudomonas sp, and Micrococcus sp. These types of bacteria can be utilized for the development of LKPD learning of Biology of SMA X class about Bacteria (KD 3.5) and change and preservation of class X Environment (KD 3.11). Testing of the use of LKPD that has been generated and the benefits of enriching student learning materials in a classical manner are highly recommended.Key Word: Identification, Bacteria, Soil Contaminated, Student Worksheet